Collected maxims and other reflections - de la Rochefoucauld, François, Duc, 1613-1680; Blackmore, A. M.; Blackmore, E. H.; Giguère, Francine (Oxford : Oxford University Press, 2008)
François de la Rochefoucauld is vooral gekend voor deze collectie uitspraken rond deugd en moraal
This is the fullest collection of La Rochefoucauld's writings ever published in English, and includes the first complete translation of the Miscellaneous Reflections. A table of alternative maxim numbers and an index of topics help the reader to locate any maxim quickly.
Tweetalig Frans/Engels.